Have the OECD Transfer Pricing Guidelines influenced the development of domestic legislation for transfer pricing and the outcome of court decisions in selected African states? - Ismail, Mohamed Waseem (Department of Finance and Tax, 2025)
The Organisation for Economic Cooperation and Development (OECD) Transfer Pricing Guidelines (TPG) is a soft law instrument that acts as a guide to many multinational entities (MNE) in applying the arm's length principle (ALP). Amongst OECD member states, the OECD TPG is a relevant instrument to provide guidance to MNEs and Tax Administrations on how to apply the ALP. In transfer pricing legal disputes, international court judgments discussing the ALP touch on the influence of the OECD TPG. Every case may vary depending on the circumstances in each case and the time the ALP was enacted as part of hard law. This paper aims to answer the question, “Have the OECD TPG influenced the development of domestic legislation for transfer pricing and the outcome of court decisions in selected African states?” A sample of literature was reviewed to understand the use of the OECD TPG as a soft law instrument within the international law landscape. Thereafter, a sample of international TP case law that references the OECD TPG was inspected to understand and analyse the stance of the OECD TPG. A systematic review was conducted on a sample of international transfer pricing court judgments to determine the weighting that the OECD TPG acts as a soft law instrument in the international tax community. A sample of African TP disputes in Ghana, Kenya, Malawi, Nigeria, South Africa, Tanzania, Uganda, Zambia and Zimbabwe was inspected to understand the status of the OECD TPG by the courts and the subsequent developments within the domestic tax legislation since the court judgment to determine whether the OECD TPG had any influence in shaping its domestic tax legislation. Through this analysis, the author attempted to understand the influential status of the OECD TPG within an African regional context despite many African countries not holding a member status with the OECD and some African countries holding observer status or act as key partners with the OECD. Where the domestic TP tax legislation lacks guidance on the application of the ALP, the OECD TPG does hold a higher status in most OECD member countries. The status of the OECD TPG varies across different jurisdictions in the sample of countries selected. It should be noted that the case law inspected is not exhaustive of the court decisions discussing the ALP for all African countries. The OECD TPG status within Africa started as a soft law instrument, but over time, it has proven to be a focal area in developing TP regulations and the domestic TP tax legislative frameworks in Africa.